Analisa Kebutuhan Air Minum Kampus Binawidya Universitas Riau Pekanbaru - Ahmad, Ghiffari; Asmura, Jecky; Andrio, David (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Water is an important requirement in day life. Meet the needs of clean water Campus University of Riau currently uses only ground water that comes from bored wells. The dringking water for academic community of the campus uses water refill. The planning for dringking water supply system of Riau University campus aims to complete the water needs for academic community of Riau University with dringking water quality. The bored water will become of raw water into dringking water treatment plant with the installation site water treatment plant located east of the university faculty of fisheries Riau (0o28â47,62âN 101o23â05,24âE). The planning was done 10 years periode, with the total flowrate 6,58 L/s. Result of the treatment planned consist of bored well,neutralization, filtration (rapid sand filter), reverse osmosis, desinfection, and reservoir. The cost required to build a system of drinking water treatment plants campus University of Riau are Rp 2.405.454.302,00.Keywords: Water drinking, water treatment plant, campus University of Riau